The relationship between high school students' liking of elements in alcohol advertising and advertising effectiveness - Fielder, Lynda Jane (Curtin University, 2011)
The increasing level of alcohol consumption among youth and related harms is an issue of international public health concern (Hingson, Heeren, Winter, & Wechsler, 2005; Jernigan & Mosher, 2005; Jernigan, Ostroff, & Ross, 2005; Mosher, 2006; Room, Babor, & Rehm, 2005; World Health Organization, 2004a). Many factors influence youth alcohol consumption, including social, individual, structural and marketing factors (Donovan, 1997). Research shows that alcohol advertising reinforces positive attitudes toward youth drinking and plays a significant role in their decision to drink, as well as level of consumption (Anson, 2010; Babor et al., 2003; Hurtz, Henriksen, Wang, Feighery, & Fortmann, 2007; Jernigan et al., 2005).A number of countries follow a regulatory code of advertising in relation to alcohol. Self-regulatory codes are used to prohibit marketing that targets underage youth (Distilled Spirits Industry Council of Australia Inc., 2010). However, the effectiveness of these codes and self-regulation in general has been questioned in the literature (Jones & Donovan, 2002; Jones & Jernigan, 2010; US Department of Health and Human Services, 2007; World Health Organization, 2009a, 2009b). In Australia, the Alcohol Beverages Advertising (and Packaging) Code (ABAC) is the specific code that regulates the content of alcohol advertising (The ABAC Scheme, 2011). While a few studies have assessed alcohol advertising content against these codes (Donovan, Donovan, Howat, & Weller, 2007; Jones & Donovan, 2002), to date, no studies have attempted to relate identified breaches of codes contained in alcohol advertisements and the subsequent impact on advertising effectiveness.The aim of this study was to explore the relationship between high school students' liking of elements in alcohol advertising and advertising effectiveness. A total set of 25 alcohol advertisements was selected from advertisements frequently aired during the period November 2005 to October 2006 (15 beer advertisements; 9 spirits advertisements; 1 sparkling wine advertisement).Content analysis of the 25 advertisements revealed that all contained at least one element with known appeal to children and underage youth, indicating that youth in Australia are being exposed to alcohol advertisements that would be in breach of the Alcohol Beverages Advertising Code (ABAC). These advertisements were exposed to a sample of 544 young people attending Years 8 to 10 in public secondary schools in the Perth metropolitan area. Each student was exposed to five of the alcohol television advertisements. Respondents’ individual reactions to each alcohol advertisement were obtained using a confidential, self-completion questionnaire. This instrument was also used to record respondents’ alcohol beverage preferences.The attractiveness of specific execution elements in the advertisements significantly predicted advertising likeability, which in turn predicted advertising effectiveness. Advertisements for the most preferred brands were characterised by: music; animal/animation; visual appeal; special effects; and humour.These findings support other studies in suggesting that the current Australian system of advertising self regulation is inadequate in protecting underage youth from exposure to alcohol advertising. Recommendations from the results of this study are that the current voluntary system should incorporate further restrictions in content and programming zones and that consideration be given to a mandatory system with substantial penalty powers.